Coastal shipping during the pandemic: Spatial assessment of the demand for passenger maritime transport - Boile, Maria; Theofanis, Sotirios; Perra, Vasiliki-Maria; Kitsios, Xenophon (Frontiers in Future Transportation, 2023)
Coastal shipping plays a key role in insular regions, ensuring economic, territorial and societal cohesion at national and regional level and supporting the transport of passengers, vehicles and goods. For Greece, passenger maritime transport is essential, considering its lengthy coastline (about 15,000 km) and its numerous islands, scattered within its territorial waters. This paper investigates demand for passenger maritime transport of the Greek coastal shipping before and during the pandemic through a spatial assessment based mainly on primary data provided by the responsible National Authority, thus highlighting issues to be addressed through policy and decision making. Considering that Covid-19 led to significant disruption of transport services, especially in ferry operations, demand for passenger maritime transport was almost halved during 2020. However, the supply services provided are mostly determined by the terms of the public service obligations (PSOs) that are announced by the responsible National Authority and which had to be further enhanced during the pandemic for sufficiently covering the corresponding demand. As such, the paper aims to support policy and decision making, and the implementation of relevant strategies and measures so as to maintain the proper level of services provided in the sector during emergencies.